The Seasonal KPSS Test When Neglecting Seasonal Dummies: A Monte Carlo analysis - Ghassen El Montasser; Talel Boufateh; Fakhri Issaoui (Economics and Econometrics Research Institute (EERI), 2013)
This paper shows through a Monte Carlo analysis the effect of neglecting seasonal deterministics on the seasonal KPSS test. We found that the test is most of the time heavily oversized and not convergent in this case. In addition, Bartlett-type non-parametric correction of error variances did not signally change the test's rejection frequencies.
Keywords: C32; 330; Deterministic seasonality; Seasonal KPSS Test; Monte Carlo Simulations